Pengaruh Waktu Pelapisan Spermatozoa Sapi Pada Media TALP yang Disuplementasi bovine serum albumin (BSA) Terhadap Jenis Kelamin Embrio In vitro - T. Afriani; Z. Udin; Jaswandi Jaswandi; S. Asmairicen (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2011)
This research aim to know the influence of depth veneering time of spermatozoa at media of TALP which was supplemented by 4% BSA to embryo gender in in- vitro and to get the time dissociation of spermatozoa which have the best chromosome Y. This research represent attempt of exsperiment in RBT by 4 time veneering of spermatozoa as treatment, times intake of semen of epididymis to groups. Variables measure are: 1). mortality of spermatozoa, 2). number of in vitro fertilzation, 3. masculine gender embryo ratio. Result shown, the veneering of cow spermatozoa during 90 minute in media of TALP which was supplemented by 4% bovine serum albumin (BSA) can dissociate spermatozoa which have chromosome Y with percentage of highest male sex (90.00±24.49), and highest percentage of mortality and fertility were obtained at veneering during 60 minute with scoring 73.33 ± 5.16 and 53.92±18.79 respectively.